Aspirin and extended-release dipyridamole versus clopidogrel for recurrent stroke - Sacco, Ralph L.; Diener, Hans-Christoph; Yusuf, Salim; Cotton, Daniel; Ounpuu, Stephanie; Lawton, William A.; Palesch, Yuko; Martin, Renée H.; Albers, Gregory W.; Bath, Philip M.W.; Bornstein, Natan; Chan, Bernard P.L.; et al. (Massacheutts Medical Society, 2008)
Background Recurrent stroke is a frequent, disabling event after ischemic stroke. This study compared the efficacy and safety of two antiplatelet regimens — aspirin plus extendedrelease dipyridamole (ASA–ERDP) versus clopidogrel. Methods In this double-blind, 2-by-2 factorial trial, we randomly assigned patients to receive 25 mg of aspirin plus 200 mg of extended-release dipyridamole twice daily or to receive 75 mg of clopidogrel daily. The primary outcome was first recurrence of stroke. The secondary outcome was a composite of stroke, myocardial infarction, or death from vascular causes. Sequential statistical testing of noninferiority (margin of 1.075), followed by superiority testing, was planned. Results A total of 20,332 patients were followed for a mean of 2.5 years. Recurrent stroke occurred in 916 patients (9.0%) receiving ASA–ERDP and in 898 patients (8.8%) receiving clopidogrel (hazard ratio, 1.01; 95% confidence interval [CI], 0.92 to 1.11). The secondary outcome occurred in 1333 patients (13.1%) in each group (hazard ratio for ASA–ERDP, 0.99; 95% CI, 0.92 to 1.07). There were more major hemorrhagic events among ASA–ERDP recipients (419 [4.1%]) than among clopidogrel recipients (365 [3.6%]) (hazard ratio, 1.15; 95% CI, 1.00 to 1.32), including intracranial hemorrhage (hazard ratio, 1.42; 95% CI, 1.11 to 1.83). The net risk of recurrent stroke or major hemorrhagic event was similar in the two groups (1194 ASA–ERDP recipients [11.7%], vs. 1156 clopidogrel recipients [11.4%]; hazard ratio, 1.03; 95% CI, 0.95 to 1.11). Conclusions The trial did not meet the predefined criteria for noninferiority but showed similar rates of recurrent stroke with ASA–ERDP and with clopidogrel. There is no evidence that either of the two treatments was superior to the other in the prevention of recurrent stroke. (ClinicalTrials.gov number, NCT00153062.)